PENGEMBANGAN MODUL BERBASIS HOTS PADA TEMA 6 MATERI MEMBANDINGKAN SIKLUS MAKHLUK HIDUP KELAS IV SEKOLAH DASAR - Siwi Purwanti; Riri Zulia Anggraini Putri (Universitas PGRI Yogyakarta, 2021)
Based on the observations and the interviews with fourth-grade teachers of Muhammadiyah Semoya Elementary School, there were limitations to the HOTS-based module media on the sixth theme of learning 1:Cita-citaku (my future goals); first sub-theme: Aku dan Cita-citaku (me and my future goals). The students found it challenging to understand the material on comparing the cycles of living things. This study aimed to develop and determine the High Order Thinking Skill (HOTS) of students in the Natural Science subject (IPA) to compare the cycle of living things for grade IV of elementary school. The type of research used in this study was Research and Development (R&D). The development steps used was Sugiyono's theoretical model (2018: 773). as for the research stages: potentials and problems, data collection, product design, design of validation, design of revision, product manufacturing, and product of revision. Data collection techniques were interviews, observation, and expert assessment questionnaires. Data analysis techniques used were quantitative data and qualitative data. The results showed that media experts' feasibility assessment was 85%, material experts 84%, learning experts73%.In the quantitative assessment, it was in a very feasible category. Following the suggestions and criticisms of media experts, material experts, and learning experts, HOTS-based module media was suitable for learning-medium in fourth-grade elementary school students' teaching and learning process.